African immigrant child health: A scoping review - C. Fouche; S. Richter; H. Vallianatos; A. Mason; H. Fernández-Sánchez; V. Mazzucato; M. Kariwo; B. Salami (Elsevier, 2021)
The health of migrant children is a pressing issue. While most African migration takes place within Africa, a significant number of African migrants travel to outside of the continent. This article reports findings from a scoping review on the health of African immigrant children from sub-Saharan Africa now living outside of Africa. A systematic search for studies published between 2000 and 2019 resulted in only 20 studies reporting on the health of children up to 18 years of age migrating from sub-Saharan Africa. Data from these articles were thematically analyzed, highlighting concerns related to the children's nutrition status (n = 8), mental health (n = 7), and physical health (n = 5). Study participants were primarily from Somali and Ethiopia, and most studies were conducted in Australia or Israel. The review highlights several gaps related to the scope, range, and nature of evidence on the health of African immigrant children living outside of Africa. In particular, most focus on children's nutritional and mental health, but pay little attention to other health concerns this specific population may encounter or to the benefits associated with effective responses.